Nierozłączny duet: socjalistyczne w treści i narodowe w formie - Stojak, Grażyna (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2019)
The paper is a reflection on the conditions in which post-war architects had to work in the third quarter of the 20th century. It was a time when the pre-war school of modernist architectural design had been done away with, and trends and achievements of modern European architecture were rejected. Instead, they were replaced with designing guidelines invented in the USSR and ready Soviet patterns. The article shows how architectural solutions of the time were used when building cultural institutions in towns, using the example of three selected culture centres in the former Rzeszów province. The first centres were built with the help of the local Communist Party activists and financial support from large factories: The Stalowa Wola Steelworks Culture Centre in Stalowa Wola (1952), Transport Equipment Factory Culture Centre in Rzeszów (1953) and Transport Equipment Factory Culture Centre in Mielec (1953). They were built from scratch according to Soviet patterns and adapted to the needs of the region.
The inseparable duo: socialist in content and national in form
Keywords: architecture; socialist realism; culture centres; Soviet patterns